Thermal crosstalk investigation in photonic integrated circuits - Lin, Junjie (Nanyang Technological University, 2021)
The report reviews the effect of thermal crosstalk and thermal rectification on photonic integrated circuits. Simulations will be done using the DEVICE, MODE and INTERCONNECT modules of the Lumerical software. The report aims to produce models of structures within photonic integrated circuits to simulate its function and study the difference in output due to thermal crosstalk. DEVICE is used to simulate thermal distribution; MODE is used to simulate physical properties of waveguides and these data will be the input for the circuit built in INTERCONNECT to produce the outputs. After the simulation of thermal crosstalk, simulation on thermal rectification will be done using the same modules and models in the previous simulation. Thermal rectification is a new proposed method to offset the effect of thermal crosstalk and various advantages over current solutions such as thermal isolation trench and athermal optical waveguide. Two sets of simulation will be done where one simulates thermal rectification without inducing additional thermal crosstalk while the other set simulates the case where additional thermal crosstalk will be induced. From the simulation results, graphs will be plotted to analyze and compare the dat a . The trends between various parameters such as relationship between distance a nd temperature, distance and thermal crosstalk, distance and compensation will be analyzed. Finally, the advantage and limitations of thermal rectification as well as possible options for further study will be presented.